Reproductive development of Krapfia weberbaueri(Ranunculaceae) under controlled conditions of light and temperature - Roca, Beatriz (2013)
Krapfia weberbaueriStandl. & J. F. Macbr. is an endemic species from Peru, categorized as vulnerable, and distributed in the departments of Ancash, Huanuco, Junin and San Martin. This work reports the reproductive development of the species under controlled conditions of light and temperature (12 hours light/12 hours darkness, 12 °C during light hrs and 8 °C during dark hrs). Entire plants at reproductive stage were collected at Cordillera Blanca (Ancash), where it is found forming patches, at an elevation of 4200 to 4800 m. The species has large and showy flowers, which from anthesis to the onset of senescence remain responsive, however at a greater extent in the mature flower, stage at which the dehiscence of stamens and release of pollen grains reaches 100%. This period lasts a total of 13 days. Nectar production begins when the flower matures and continues until the total senescence of petals. The viability of the pollen grains varied from 78 to 97% and success in achene production was 38-62%. It may be noted that pollination is favored by the final position of anthers over the stigmas, nectar production, moderate presence and movement of mites and aphids, and the pendulous position of the flower.